2015
DOI: 10.2217/nnm.14.231
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulations for Therapy of Pancreatic and Liver Cancers

Abstract: Pancreatic and liver cancers often have poor prognoses. Clinically, pancreatic and liver cancer requires early diagnosis, and surgery is often associated with tumor recurrence. Currently, chemotherapies are limited in their ability to accurately target the tumors, and are associated with significant toxicity in patients. Targeting of chemotherapy can be improved by encapsulation in nanocarriers. A variety of preclinical studies indicate relatively superior therapeutic outcomes compared with drug alone therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Nanoparticle carriers with appropriately tailored physico chemical characteristics (including optimal size, charge, shape, and drug loading and release), which can protect their cargo (the drug) from premature release and degradation, and can traverse the various biological barriers to drug delivery, have the potential to improve therapeutic efficacy in patients with PDAC (BOX 2). Indeed, advances in nanotechnology have been leveraged for improved drug-delivery strategies for a variety of therapeutic and diagnostic agents 18 . For example, several nano formulations of gemcitabine have been evaluated in preclinical and clinical studies [19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Nanoparticle carriers with appropriately tailored physico chemical characteristics (including optimal size, charge, shape, and drug loading and release), which can protect their cargo (the drug) from premature release and degradation, and can traverse the various biological barriers to drug delivery, have the potential to improve therapeutic efficacy in patients with PDAC (BOX 2). Indeed, advances in nanotechnology have been leveraged for improved drug-delivery strategies for a variety of therapeutic and diagnostic agents 18 . For example, several nano formulations of gemcitabine have been evaluated in preclinical and clinical studies [19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Human hepatocellular carcinoma (HCC) is a common type of primary liver cancer and is diagnosed in more than half a million people worldwide ( de Souza et al, 2015 ). At present, HCC has received increasing attention because of its important effect on the physiological functions of the liver, high lethality, and the growing incidences in many regions ( Torre et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The organelles inside the cells are simplified for a better demonstration, intracellular organelles images are taken with permission from Servier Medical Art In the case of chemotherapeutics many lack specificity for the proposed site of action resulting in both healthy and cancerous cells being affected, which leads to debilitating side effects. Nano carrier systems, with ability to preferentially deliver and trap chemotherapeutics in tumour site thus minimising the exposure of healthy tissues to the cytotoxic drugs, are proposed as ideal vectors tomitigate the incidence and severity of side effects (2). The phenomenon is referred to as the enhanced permeation and retention (EPR) effect, which is due to the immature vasculature system in tumours (Figure 1-1).…”
Section: Declaration By Authormentioning
confidence: 99%
“…US exposure study design: US is applied from underneath of well in a 24 well plate, a coupling gel was used between the US probe and well plateIt was observed that using JUS2 at its highest intensity (i.e. intensity of 2.5 W/cm2 and 100% duty cycle), any volumes more than 2.25 mL/well (in a 24 well plate) would lead to formation of condensate (as a result of agitation caused by US) on the ceiling of the lid inserted over the samples. This could consequently change the final volume of the samples causing variations between each treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation